Farmer producer companies fermenting new wine for new bottles - Shah, Tushaar (2016)
India’s track record of forming robust, self-sustaining farmer cooperatives has been poor ever since the early 1900s when the movement began. For long, restrictive laws were blamed for their failure. But most of the 2,000 farmer producer companies registered under a new amendment to the Companies Act 1956 appear like old wine in a new bottle. This article explores why, and argues for the need to focus on the logic and process of promoting new farmer cooperatives to improve their success rate.